Comportement saisonnier du betail zebu en Adamaoua Camerounais. I. Etude des femelles adultes:comparaison de la race locale aux metis demi-sang Brahma - Lhoste, Philippe (1967)
The influence of some ecological and physiological factors on weight of cows at Wakwa station in Cameroon were studied in a year. Two populations genetically different were compared: 110 cows of the local Foulani breed and 134 cows of ½ breed Brahman x Foulani. The following conclusions were drawn: The ponderal growth of the cow occured up to 8-9 years; in extensive rearing the alterations of the seasons resulted in great weight variations of the cows, some animals showed, in undernutrition period, a loss of 1/3 of their weight and had severely suffered; the season of calving seems to be an influent factor of the weight variation; and calving occured early in the rainy season.